Hybrid genome assembly of colistin-resistant mcr-1.5-producing Escherichia coli ST354 reveals phylogenomic pattern associated with urinary tract infections in Brazil - Bruna Fuga; Fábio P. Sellera; Fernanda Esposito; Quézia Moura; Marcelo Pillonetto; Nilton Lincopan (Journal of Global Antimicrobial Resistance, 2024)
ABSTRACT: Background: The rapid and global spread of Escherichia coli carrying mcr-type genes at the human-animal-environmental interface has become a serious global public health problem. Objective: To perform a genomic investigation of a colistin-resistant E. coli strain (14005RM) causing urinary tract infection, using a hybrid de novo assembly of Illumina/Nanopore sequence data, presenting phylogenomic insights into the relationship with mcr-1-positive strains circulating at the human-animal-environmental interface, in Brazil. Methods: Genomic DNA was sequenced using both the Illumina NexSeq and Nanopore MinION platforms. De novo hybrid assembly was performed by Unicycler. Genomic data were assessed by in silico prediction and bioinformatic tools. Results: The genome assembly size was 5 333 039 bp. The mcr-1.5-positive E. coli strain 14005RM belongs to the sequence type ST354 and presented a broad resistome (antibiotics, heavy metals, disinfectants, and glyphosate) and virulome. The mcr-1.5 gene was carried by an IncI2 plasmid (p14005RM, sizing 65,458 kb). Full genome SNP-based phylogenetic analysis reveals that mcr-1.5-producing E. coli strain 14005RM is highly related (> 98% identity) to colistin-resistant mcr-1.1-positive ST354 lineages associated with urinary tract infections in Brazil since 2015. Conclusion: Mobile colistin resistance within the Brazilian One Health microbiosphere is mediated by mcr gene variants propagated by IncX4, IncHI2, and IncI2 plasmids, circulating among global clones of E. coli.